2018
DOI: 10.1136/bmjopen-2017-020448
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Social Interaction in Depression (SIDE study): protocol of a randomised controlled trial on the effects of a Cognitively Based Compassion Training (CBCT) for couples

Abstract: IntroductionPositive social interactions (PSIs) and stable relationships can exert substantial benefits on health. However, patients suffering from depression benefit less from these health-promoting effects. Moreover, relationship quality and even partners’ health has been found to be negatively affected by depressive symptomatology, which may result in overall impairments in social functioning of a romantic couple. Psychobiological research indicates that these impairments may be accompanied by a maladaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 114 publications
0
17
0
1
Order By: Relevance
“…Besides mindfulness, other contemplative practices such as compassion have been recently designed as contemporary forms of secular trainings with a specific relational focus (Aguilar‐Raab et al, 2018; CCSCBE, 2019; Collins et al, 2018). Compared with mindfulness, compassion directly emphasizes social interconnectedness and has been shown to further prosocial attitudes and behavior (Gilbert, 2014; Leiberg et al, 2011; Quaglia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Besides mindfulness, other contemplative practices such as compassion have been recently designed as contemporary forms of secular trainings with a specific relational focus (Aguilar‐Raab et al, 2018; CCSCBE, 2019; Collins et al, 2018). Compared with mindfulness, compassion directly emphasizes social interconnectedness and has been shown to further prosocial attitudes and behavior (Gilbert, 2014; Leiberg et al, 2011; Quaglia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculations for the SIDE studies were tailored for the conduction of the subsequent RCT that would further include the DCs who participated in the present study. Analyses with G*Power ( 97 ) were described in the study protocol and revealed an optimal total sample size of N = 50 DCs, accounting for assumed attrition ( 73 ). In the present study, we aimed at recruiting an equal amount of N = 50 additional NDCs for the comparison of PAT responses.…”
Section: Methodsmentioning
confidence: 99%
“…The SIDE studies contained a cross-sectional, first part in which self-report, psychobiological, and eye-tracking data was collected from DCs and NDCs, and an interventional, second part where participating DCs were randomized to either a 10-week Cognitively Based Compassion Training (CBCT ® ) for couples or to a control treatment. Procedures and methods of this randomized controlled trial (RCT) can be found in the published study protocol (73). No protocol was pre-registered for the cross-sectional part, which is reported here, but many of the present methods (e.g.…”
Section: Study Design and Ethicsmentioning
confidence: 99%
See 2 more Smart Citations